Geographically predominant genotypes of Aspergillus terreus species complex in Austria: s microsatellite typing study. (March 2016) - Lackner, M.; Coassin, S.; Haun, M.; Binder, U.; Kronenberg, F.; Haas, H.; Jank, M.; Maurer, E.; Meis, J.F.; Hagen, F.; Lass-Flörl, C.
Abstract: Aspergillus terreus species complex is recognized as a frequent agent of invasive aspergillosis in Tyrol. The reason for this specific epidemiological situation is unclear. Aspergillus terreus strains isolated from environmental and clinical sources were genotyped using a novel panel of short tandem repeats and were evaluated for virulence. Three major endemic genotypes collected from the Inn region and its side valleys were found to cause the majority of invasive A. terreus infections. All of these genotypes were of the same mating type, which suggests that a mating barrier is present between these geographically well-adapted strains which is found to persist for at least 11 years. The three major genotypes were prevalent in both human infections and the environment. No major differences in virulence were observed using Galleria mellonella as model. Our data suggest a specific environmental exposure being responsible for the high incidence of A. terreus infections in Innsbruck, the Inn valley and side valleys (Tyrol, Austria).